The Perception of Students on The Need for Entrepreneurship Education in Teacher Education Programme (Global Journal of Human-Social Science, 2013)
The study investigated the need for entrepreneurship Education in the Teacher education programme as perceived by Federal College of Education Students Osiele Abeokuta Ogun State Nigeria The Study employed the descriptive survey research design The sample consisted of two hundred college of education students selected using stratified random sampling techniques One research question and three null hypotheses guided this study A twenty item questionnaire was used for data collection Its validity and reliability were established using cronbachi s alpha The value got was 0 81 Its reliability co-efficient was found to be 0 85 The data collected were analyzed using percentages mean and t-test statistical tools The results indicated that College of Education Students perceived entrepreneurship education as very important to their programme of study because it affords them the opportunity to be innovative resourceful self-reliant self-employed and leaders that can stand the test of time in their future endeavour